Analisis Sosiologi Terhadap Konflik Antar Umat Beragama: Sociological Analysis of Interfaith Conflicts - Haikal Al Fiqri (SOSIOLOGIA : Jurnal Agama dan Masyarakat, 2024)
Religion is one of the important things in human life. The provisions and laws in religion bind its adherents to act in accordance with the guidelines that have been set. All religions in the world coexist in a frame of tolerance to create a safe and peaceful life. However, there are still many conflicts between religious communities in certain areas. One way to solve the problem is with a sociological approach. This researcher uses descriptive-analysis of library research. The results of this study indicate that conflicts between religions occur because of anthropocentrism in religion, stereotypes of religion, understanding of the religion they adhere to. lack of religious understanding of other religions. So that they consider other religions only as negative knowledge. So that the efforts that need to be made are to open communication and dialogue with adherents of other religions to build a developed, just, prosperous country with religious integrity.